Synergistic effect of WRI1 and DGAT1 coexpression on triacylglycerol biosynthesis in plants. Issue 4 (8th January 2013) - Vanhercke, Thomas; El Tahchy, Anna; Shrestha, Pushkar; Zhou, Xue-Rong; Singh, Surinder P.; Petrie, James R.
Abstract : Metabolic engineering approaches to increase plant oil levels can generally be divided into categories which increase fatty acid biosynthesis ('Push'), are involved in TAG assembly ('Pull') or increase TAG storage/decrease breakdown ('Accumulation'). In this study, we describe the surprising synergy when Push (WRI1) and Pull (DGAT1) approaches are combined. Co‐expression of these genes in the Nicotiana benthamiana transient leaf expression system resulted in TAG levels exceeding those expected from an additive effect and biochemical tracer studies confirmed increased flux of carbon through fatty acid and TAG synthesis pathways. Leaf fatty acid profile also synergistically shifts from polyunsaturated to monounsaturated fatty acids. Abstract : ► Co‐expressing the Arabidopsis thaliana DGAT1 acyltransferase and WRI1 transcription factor results in a strong synergistic effect on TAG accumulation. ► A synergistic increase in PC was not observed although WRI1, DGAT1 and the combination of both genes all resulted in significant radiolabel incorporation in this pool. ► A synergistic effect on 18:1 Δ9 increase in TAG was observed. ► Combining Push and Pull methods will likely be required for maximal increase of storage oil, especially in non‐seed tissues.